Pengaruh Modal Intelektual, Direksi Wanita, dan Jajaran Direksi Independen Terhadap Biaya Modal Pada Perusahaan Pariwisata di Indonesia - Saarce Elsye Hatane; Jane Jacinda Maitri Firman; Josephine Bianca Indrawila (Business Accounting Review, 2021)
This research intended to explain the effect of intellectual capital disclosure, independentboard, and woman on board on the cost of capital in the Indonesian tourism industry. The researchsamples were 31 Indonesian tourism industries listed on Indonesia Stock Exchange from 2015 until2019. This research used ordinary least squares panel data analysis. The main finding of this researchwas that there are positive influences of intellectual capital disclosure, and women on board on theweighted average cost of capital. On the other hand, independent boards negatively impact theweighted average cost of capital. However, none of the three independent variables has a significanteffect.